Pemanfaatan Limbah Plastik Sebagai Media Tanam dengan Metode Vertikultur Hidroponik untuk Memaksimalkan Fungsi Pekarangan di Desa Pringgabaya - Satrijo Saloko; Muhammad Nursan; Rizka Amalia; Sopiandi Sopiandi (Universitas Mataram, 2021)
Sustainable Food House is a program to optimize the use of environmentally friendly yards, and is designed to help meet family quality and nutritional needs, food diversification based on local resources, plant conservation, and increasing household income through non-rice based household creative industries for local food processing. . The objectives of this community service program (1) increase knowledge and skills, awareness and motivate the people of Pringgabaya Village, especially the group of housewives in the use of vacant land or yards, (2) apply some simple techniques for planting yards and their maintenance that can be implemented effectively. easy for the people. The types of plants that are planted in the yard are types of vegetables that can support daily needs and the rest can be sold. Methods of activities carried out include socialization, training, and practice starting from land preparation, maintenance, development, implementation and demonstration. This activity is able to encourage and increase the awareness of the group of housewives in utilizing the yard, especially using the verticulture method of hydroponics, starting from seedling to plant maintenance.